Opening the circles : the expanding wave. From the acceptability of local varieties to the language of international contexts and the implications on the work of English practitioners - Medico, Ana Gabriela (2015)
Fil: Language is a living human institution, and as such, it is constantly changing and adapting to new circumstances and environments. The purpose of this paper is to review the different models that have been proposed to follow the process through which the English language has transcended its national boundaries and became the language of international contact.